Penggunaan Obat Kumur Lidah Buaya (Aloe vera) Sebagai Penghambat Pembentukan Plak (Tinjauan Pustaka) - Ramadhani, Suci; Aulia, Rahmi Khairani; Sumantri, Dedi (Jurnal Material Kedokteran Gigi, 2022)
Periodontal disease is a common oral disease. The main cause is microorganisms that colonize in dental plaque. Dental plaque is a collection of microorganisms that form a biofilm. The most effective way to control plaque is to brush your teeth regularly and use mouthwash. Aloe vera as an herbal plant has many benefits due to its properties, such as; antiseptic, antioxidant, anti-inflammatory, analgesic, antimicrobial, and wound healing. These properties make aloe vera potential to be utilized as an anti-plaque mouthwash. The purpose of this paper is to determine and review the use of mouthwash containing Aloe vera as an inhibitor of plaque formation. Mouthwash containing Aloe vera is proven to inhibit plaque formation, due to its active compounds such as saponins, anthraquinones, phenols and flavonoids.